Healthcare Quality and Patient Satisfaction at Internaitonal Maritime Hospital-Ghana Ports and Harbours Authority (GPHA), - Inkoom, I.A (My University, 2019)
The overall aim of the study was to examine healthcare quality and patient satisfaction at the International Maritime Hospital of the Ghana Ports and Harbours Authority, Tema. The study employed mixed research approach with questionnaires as its major instrument for data collection. A total of 75 respondents participated in questionnaire administration with 74 being correctly filled and returned accordingly. Respondents included patients and healthcare providers, either nurses, doctors or administrators. The study reveals that, patients hold average expectations whilst having positive perception about the services provided by the hospital particularly in areas like reliability, assurance, responsiveness and empathy. Further, the study reveals that, patients are satisfied with the service provision of the hospital in general and specifically in areas like responsiveness, empathy, reliability and that patients highly are satisfied with the services of nurses greatly than doctors of the hospital. Following this, the study recommends that, management of the hospital should draw policies that is centered on responsiveness, reliability and assurance and empathy as this will help meet the needs and expectations of patients.
Keywords: healthcare quality; patient satisfaction; mixed research approach